Post deposition annealing effect on properties of CdS films and its impact on CdS/Sb2Se3 solar cells performance - Gopi, Sajeesh Vadakkedath; Spalatu, Nicolae; Basnayaka, Madhawa; Katerski, Atanas; Josepson, Raavo; Grzibovskis, Raitis; Vembris, Aivars; Krautmann, Robert; Krunks, Malle; Acik, Ilona Oja (Frontiers Media, 2023)
Antimony selenide (Sb2Se3) is one of the emerging photovoltaic absorber materials possessing abundance and non-toxicity as the main attributes. Following CdTe technology, CdS is a widely used partner layer for Sb2Se3 solar cells. Related to CdS/Sb2Se3 device configuration, a number of studies reported findings and challenges regarding the intermixing phenomenon at the main interface and suitability of various annealing for CdS (and related interface) and still, significant room remains in developing strategies for interface optimization and understanding of the physiochemistry behind. In this perspective, this work provides a systematic investigation of the effect of vacuum and air annealing at temperatures between 200 and 400°C on the properties of CdS deposited by chemical bath deposition and combined with Sb2Se3 absorber obtained by close-spaced sublimation the direct impact of the CdS annealing on the device performance is illustrated. It is found that by varying the annealing temperature from 200 to 400°C in both, vacuum and air ambient, the morphology of CdS changes from highly dispersed small grain structure to sintered dense grains, the band gap decreases from 2.43 to 2.35 eV and the electron density drops from ∼1018 to ∼1011 cm−3. These changes were correlated with the changes in the CdS lattice and connected with the mobility of the OH group and the presence of secondary phases in CdS layers. 200°C air annealing of CdS was found as an optimal treatment resulting in 2.8% Sb2Se3/CdS cell efficiency - a 60% boost compared to the 1.8% performance of the device with as-deposited CdS. Material and device characterization analysis is performed, providing complementary insights on the interrelation between the physicochemical mechanism of the CdS annealing processes and device functionality. --//-- This is an open-access article adakkedath Gopi Sajeesh, Spalatu Nicolae, Basnayaka Madhawa, Krautmann Robert, Katerski Atanas, Josepson Raavo, Grzibovskis Raitis, Vembris Aivars, Krunks Malle, Oja Acik Ilona, Post deposition annealing effect on properties of CdS films and its impact on CdS/Sb2Se3 solar cells performance, Frontiers in Energy Research (11), 2023, https://www.frontiersin.org/articles/10.3389/fenrg.2023.1162576, Doi 10.3389/fenrg.2023.1162576 published under the CC BY 4.0 licence.
This study was funded by the Estonian Research Council projects PRG627 “Antimony chalcogenide thin films for next-generation semi-transparent solar cells applicable in electricity producing windows,” PSG689 “Bismuth Chalcogenide Thin-Film Disruptive Green Solar Technology for Next-Generation Photovoltaics,” the Estonian Centre of Excellence project TK141 (TAR16016EK) “Advanced materials and high-technology devices for energy recuperation systems,” and the European Union’s Horizon2020 programme under the ERA Chair project 5GSOLAR grant agreement No. 952509. The article/publication is based upon work from COST Action Research and International Networking on Emerging Inorganic Chalcogenides for Photovoltaics (RENEW-PV), CA21148, supported by COST (European Cooperation in Science and Technology). Institute of Solid-State Physics, University of Latvia has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; antimony selenide; close-spaced sublimation; cadmium sulfide; post deposition annealing; thin film solar cells